Peningkatan Kemampuan Menulis Kritik Sastra Dalam Pembelajaran Bahasa Indonesia Melalui Metode Debat Pada Peserta Didik Kelas XII SMK Negeri 1 Purwojati, Kabupaten Banyumas - Purwahono, Purwahono (PANCAR, 2018)
This research is a Classroom Action Research entitled "Increasing the Literature Writing Ability in Learning Indonesian Language Through Debate Methods in Class XII Students of SMK Negeri 1 Purwojati, Banyumas Regency". The purpose of this classroom action research: to describe the improvement in the ability to write literary criticism in learning Indonesian through debate methods of class XII students of SMK Negeri 1 Purwojati, Banyumas Regency 2016/2017 academic year. The subjects of this study were all students of class XII TSM 1, amounting to 36 students consisting of 33 participants in college and 3 female students. This research was carried out through two cycles. Each cycle takes four stages, namely planning, implementation phase, observation phase, and refining the results of the action. The instrument used in collecting data uses tests and observation sheets for the activities of students and teachers. While the data analysis is descriptive quantitative and qualitative. The results showed that there was an increase in each cycle. In the pre test the average grade score was 67.67 and those who achieved complete learning were 10 students or 27.78%. After learning using the debate method, the average grade score increases in the first cycle to 70.97 and that reaches 20 students or 55.56%. Then in the second cycle the value of the class average increased again to 77.56 and those who finished learning 28 students or 77.78%. So, the ability to write novel literary criticism with the debate method in class XII TSM 1 students of SMK Negeri 1 Purwojati, Banyumas Regency showed a significant increase